Branched-Chain Amino Acid Ingestion Stimulates Muscle Myofibrillar Protein Synthesis following Resistance Exercise in Humans - Jackman, Sarah R.; Witard, Oliver C.; Philp, Andrew; Wallis, Gareth A.; Baar, Keith; Tipton, Kevin D. (Frontiers in Physiology, 2017)
The ingestion of intact protein or essential amino acids (EAA) stimulates mechanistic target of rapamycin complex-1 (mTORC1) signaling and muscle protein synthesis (MPS) following resistance exercise. The purpose of this study was to investigate the response of myofibrillar-MPS to ingestion of branched-chain amino acids only (i.e., without concurrent ingestion of other EAA, intact protein or other macronutrients) following resistance exercise in humans. Ten young (20.1 ± 1.3 y), resistance-trained men completed two trials, ingesting either 5.6g branched-chain amino acid (BCAA) or a placebo (PLA) drink immediately after resistance exercise. Myofibrillar-MPS during exercise recovery was measured with a primed, constant infusion of L-[ring13C6] phenylalanine and collection of muscle biopsies pre and 4h post drink ingestion. Blood samples were collected at time-points before and after drink ingestion. Western blotting was used to measure the phosphorylation status of mTORC1 signaling proteins in biopsies collected pre, 1h- and 4h-post drink. The percentage increase from baseline in plasma leucine (300 ± 96%), isoleucine (300 ± 88%) and valine (144 ± 59%) concentrations peaked 0.5h-post drink in BCAA. A greater phosphorylation status of S6K1Thr389 (P=0.012) and PRAS40 (P=0.043) was observed in BCAA than PLA at 1h post drink ingestion. Myofibrillar-MPS was 22% higher (P=0.012) in BCAA (0.110 ± 0.009 %/h) than PLA (0.090 ± 0.006 %/h). Phenylalanine Ra was ~6% lower in BCAA (18.00 ± 4.31 μmol·kgBM-1) than PLA (21.75 ± 4.89 μmol·kgBM-1; P=0.028) after drink ingestion. We conclude that ingesting branched-chain amino acids alone increases the post-exercise stimulation of myofibrillar-MPS and phosphorylation status mTORC1 signaling.